2016
DOI: 10.4251/wjgo.v8.i10.745
|View full text |Cite
|
Sign up to set email alerts
|

Where does chemotherapy stands in the treatment of ampullary carcinoma? A review of literature

Abstract: Ampullary carcinoma (AC) is a rare gastrointestinal tumor without clear treatment recommendations. The management of this tumor is usually extrapolated from the treatment of pancreatic, biliary duct and intestinal cancers. Few papers have studied the AC as an independent entity and yet succombs to several limitations. These studies were retrospective single institutional experiences with limited sample sizes recruited over a long period of time. Unlike metastatic ACs where chemotherapy is the only recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Currently, treatment guidelines for advanced disease in patients with ampullary cancer have not been fully defined, and most treatment protocols are extrapolated from those established for pancreatobiliary and intestinal cancers. 57 Recently, the introduction of checkpoint immunotherapies has revolutionized the oncologic targeted therapy paradigm in various organs. 58 There is robust literature regarding PD-L1 signaling as a major immune checkpoint target for immunotherapy in MMRdeficient colorectal cancer, 5,59 as deficiencies in MMR lead to hypermutated tumors/high tumor mutation burden, which is strongly correlated with clinical response to treatments with anti-PD-L1 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, treatment guidelines for advanced disease in patients with ampullary cancer have not been fully defined, and most treatment protocols are extrapolated from those established for pancreatobiliary and intestinal cancers. 57 Recently, the introduction of checkpoint immunotherapies has revolutionized the oncologic targeted therapy paradigm in various organs. 58 There is robust literature regarding PD-L1 signaling as a major immune checkpoint target for immunotherapy in MMRdeficient colorectal cancer, 5,59 as deficiencies in MMR lead to hypermutated tumors/high tumor mutation burden, which is strongly correlated with clinical response to treatments with anti-PD-L1 therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients with pancreatic and biliary cancers, patients with AC generally have a higher surgical resectability rate and a more favorable prognosis. Current adjuvant therapy and the treatment of advanced disease for patients with AC have not been fully defined, and most treatment protocols are extrapolated from established treatment protocols for pancreatic, biliary, and intestinal cancers . These points underpin the need for better characterization of this disease through genomic evaluations to further explore therapeutic targets and facilitate improvements in outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be a significant prog nostic factor [31,32]. Chang et al [32] in his cohort showed prognostic di versity in these subtypes.…”
Section: Type Of Complicationmentioning
confidence: 99%
“…Due to the rarity of the dis ease, there are no estimated clear guidelines for adjuvant treatment of the adenocarcinoma of the ampulla of Vater by oncologic committees [31]. Moreover, approaches are different in the US and in Europe.…”
Section: Type Of Complicationmentioning
confidence: 99%
See 1 more Smart Citation